The Challenges of Narrowing the US Current-Account Deficit and Implications for Other Economies - Brook, Anne-Marie (OECD Publishing, 2005)
This article uses the OECD's interlink model to explore several possible channels through which a narrowing of the US current account deficit could occur. The shocks considered include dollar depreciation, fiscal consolidation, and an improvement in the non-price competitiveness of US producers. A key conclusion is that shocks would have to be very large in order to materially reduce the US external deficit, largely because of the offsetting impact of second-round effects. In addition...
Keywords: Economics